Healing of surgically created ulna defect treated with bone graft substitutes in a pigeon model - Ahmed, Tunio (2013)
The use of demineralized bone matrix (DBM) avian source either in the form of powder, chip, or tubular in experimental studies on pigeon models has proven to be osteoinductive. Fracture is a break in the continuity of the bone and comminuted fractures are commonly observed in birds. In case of bone loss due to fracture,ultimately to bring the broken bones to its normal function is needed for the survival of birds. Pigeons (Columba livia) with a mean body weight of 283.7617.53g were used in this study. Eighty-one pigeons were divided into Study-1 and Study-2. In Study-1, 16 and in Study-2, 65 birds were used. Extra four pigeons were sacrificed for DBM preparation for critical sized defect (CSD) healing. The hypothesis of Study-1 was that the external skeletal fixators (ESF) would stabilize the non-critical sized defect (NCSD) ulna fracture and thus leads to clinical union in a pigeon model.Therefore, the objective of this study was to evaluate the speed of the fracture healing,and quality of the union by radiology, histology and biomechanical examination in a NCSD ulna fracture stabilized with ESF in a pigeon model. In Study-1, NCSD was created in left ulna and the fracture was fixed with ESF. Sixteen birds in this study were divided into three groups. Group 1 (n=4) for 3 weeks, Group 2 (n=4) for 6 weeks and Group 3(n=8) for 12 weeks. The bone healing in these birds wereevaluated through radiological, histological and biomechanical examinations. After euthanasia at each end-point, healed specimens were dissected and fixed in 10% formalin for histological examination. The hypothesis of Study-2 was that combination of osteoinductive (DBM) and steoconductive [Bio-Oss and hydroxyapatite (HA)] biomaterials would hasten osteogenesis and clinical union incri tical sized defect (CSD) in pigeon ulna. Therefore, the objective study-2 was to monitor the radiographic, histologic and biomechanical healing progress as a result of the application of osteoinductive (DBM) and osteoconductive (Bio-Oss or HA) bone grafts implanted in CSD and stabilized with ESF in a pigeon ulna. Sixty-five birds were divided into five groups namely Group 1 (DBM), Group 2 (Bio-Oss ), Group 3 (HA), Group 4 (DBM+Bio-Oss) and Group 5 (DBM+HA). A 1 cm CSD was created at the mid-shaft of the left ulna and defects were treated as per design and stabilized with ESF. All the experiments were performed under Isoflurane inhalation anaesthesia. After euthanasia of birds at each end-point of the experiment, the grafted sites were removed. The specimens (n=16) were evaluated by radiography, histology and biomechanics. The specimens were fixed in 10% neutral buffered formalin and decalcified in 5% formic acid for histological purpose. Results of the radiographic assessment in Study 1 showed clinical union at week 3 in 50% of the birds. At 6 and 12 weeks, all the pigeons showed good clinical union (100%) and less callus formation or primary bone union. Histological assessment on the NCSD at 3 weeks revealed bridging of callus and bone union of the callus in all of the birds except for 2 birds, where only the trabecular bone was formed. At 6 and 12 weeks, there was minimal callus, good alignment and excellent clinical union of the bone. A 3-point bending test at 12 weeks of the NCSD healed ulna (n=4) showed, maximum flexure load and the flexure stress at the maximum load were significantly (p<0.05) higher in the intact right ulna (n=4) compared to the left ulna (n=4), while the flexure stress and the flexure strain at the break were not significantly different (p>0.05). External skeletal fixators provided good mechanical strength to the operated ulna in all groups and can be used for further bone graft experiments. From Study-1, it can be concluded that bone healing proceeds more rapidly if bird fracture fixed with ESF and could be useful for avian clinical fracture management. In study-2, radiographic results of CSD treated with DBM (Group 1), observed at 3 and 6 weeks, showed no significant (P>0.05) difference in CSD healing in all birds. At 12 weeks only 50% birds showed clinical union (n=4/4). Using DBM alone showed good cortical union at week 12. In the Bio-Oss (Group 2) at week 3 there was no significant (P0.05) difference was observed within the group; but at week 6,there was some evidence of periosteal callus. At week 12 Bio-Oss showed a significant difference (P<0.05) compared to 3 and 6 weeks. In HA (Group 3) after 3 and 6 weeks of graft healing, radiographs showed no significant difference (P>0.05) was observed, but there was a significant (P<0.05) difference in CSD healing at week 12 with HA graft. Fifty percent of the CSD healing occurred at week 12. In DBM+Bio-Oss (Group 4), after 3 weeks, healing there was no significant (P>0.05) bone formation. After 6 weeks, CSDs were completely filled with radiodense material but there was no new bone formation with this combination. At week 12 there was improved bone graft healing but it was no difference when the same bone grafts were used alone. Demineralised bone matrix + Bio-Oss did not lead to faster clinical union. In DBM+HA (Group 5), there was no change in the defect healing at 3 and 6 weeks post-grafting. At 12wks there was CSD healing and radiodensity, but no clinical union. Birds were sacrificed at each end-point using 0.3 ml of Pentobarbital (Lure Cedex,France) and the implant sites were dissected and processed for histology. Histological results of CSD healing with DBM showed formation of fibrous connective tissue and there was no significant (P>0.05) difference or similarly at week 6. Critical skeletal defect healed with fibrocartilage union and formation of new bone next to the bone graft. At week 12 of DBM healing, few sections revealed a cartilage area and some bone formation in the matrix, and mesenchymal cells had developed on the surface. With Bio-Oss at 3 weeks of healing no bone formation was seen. After 6 weeks of healing, birds showed that 100% of the CSDs were filled with Bio-Oss and formed trabecular bone and small new bones. After 12 weeks, woven bone formation was observed. In HA group at 3 and 6 weeks, the graft was encapsulated with fibrous and immature bone. After 12 weeks there was early bone ingrowth. Treatment with DBM+Bio-Oss showed little cortical development at 3 and 6 weeks. However, at week 12 good graft incorporation with the host bone occurred, but no clinical union. Demineralized bone matrix + HA treatment produced healing with fibrous connective tissue and there was very little graft incorporation at week 3. At week 6 there was no clinical union, but at week 12 the bone grafts showed excellent graft incorporation in the CSD. Healed ulna CSD with bone grafts at week 12 did not shown clinical union in all groups and all the grafted sites were too unstable to proceed with a biomechanical evaluation. In conclusion, ESF is the best choice for NCSD fracture fixation and provided excellent clinical union in pigeon ulna. The application of ESF is effective and easy to fix in cases of ulna fractures in birds and can be used for bone graft repair studies. Results based on the radiological evaluation showed that the combination of DBM with Bio-Oss as well as with HA did not hasten steogenesis or produce faster clinical union in CSD healing in pigeon ulna. Results from histological evaluation showed that the addition of Bio-Oss and HA to DBM enhanced the tendency of bone healing in the pigeon models. This study also confirmed that ESF is crucial to attain CSD healing along with bone grafts as it had stabilized the ulna bone in birds. This study showed that DBM alone provided bone union and there was evident callus formation in the CSD at 12 week post-grafting in pigeon ulna. Demineralized bone matrix (DBM) implant could be beneficial for faster fracture healing in birds since it contains bone morphogentic proteins (BMPs).